A new species of Astyanax (Characiformes, Characidae) from the upper río Bermejo basin, Salta, Argentina - Mirande, Juan Marcos (2004)
Astyanax latens sp. n., from the Bermejo river basin, is described in this paper. Astyanax latens is diagnosed by a combination of characters: somewhat rhomboidal body; presence of 24-29 branched anal fin rays; 1-4 maxillary teeth; long pectoral fins (23.2-26.6 % of SL) always reaching one third of pelvic fin; long pelvic fins (17.6-22.0 % of SL) always surpassing anal fin origin; anal fin base long (32.3-36.7 % of SL); 26-27 gill rakers on first branchial arch; lateral band extremely narrow; one large vertically elongated humeral spot and a second one very faint; relatively shallow caudal peduncle (10.0-11.4 % SL); fifth tooth of inner premaxillary series very small and scarcely posterior to main series; origin of anal fin below dorsal fin.